Pengaruh Budaya Organisasi, Dukungan Manajemen Puncak, dan Pemanfaatan Teknologi Informasi pada Kinerja Sistem Informasi Akuntansi - Raditya, I Dewa Gede Ngurah; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi; Vol 24 No 2 (2018)DO - 10.24843/EJA.2018.v24.i02.p02, 2018)
Advances in information technology in the competitive business world make accounting information systems become an important tool in the organization. There are 3 variables in this research that can affect the performance of accounting information system that is organizational culture, top management support, and utilization of information technology. This research was conducted at 22 Lembaga Perkreditan Desa in Kecamatan Sukawati. Sampling method was done by non probability sampling with purposive sampling technique. Data analysis technique used in this research is multiple linear regression analysis. The result of multiple linear analysis shows the variables of organizational culture, top management support, and the utilization of information technology have a positive influence on accounting information system performance, this means the better or higher organizational culture, top management support, and utilization of ionformation technology hence the performance of accounting information system will increase . This research provides benefits for the organization and be used as a basis in making decisions related to technological development factors, especially the performance of accounting information systems. Keywords: accounting information system performance, organizational culture, top management support, utilization of information technology